The role of social and psychological factors in shaping health behaviors among rural adolescents: a cross-sectional study - Ke Yang; Caixiu Xue; Lei Xu; Jia Wang; Xiaohui Xie; Wansha Zhou; Lianhong Wang (Scientific Reports)
Abstract This cross-sectional study investigated the association between social and psychological factors and the health behaviors of 1563 junior high school students (aged 12–16) in rural Guizhou, China. Pearson correlation analysis and linear regression analysis were used to explore these relationships. The Adolescent Health Promotion (AHP) scale was employed to evaluate the students’ health behaviors; the participants’ total average score was (125.57 ± 24.09). The correlation analysis revealed that psychological state, family, and peer resistance were significantly related to adolescents’ health behaviors. All dimensions were associated with health behaviors except for obsessive-compulsive behaviors on the psychological state measure. Grade, emotional instability, psychological imbalance, study stress, resistance to peer influence, and family closeness all influenced adolescent health behaviors. The results revealed that rural junior high school students in China engage in a moderate level of health behaviors, leaving much room for improvement. Schools, families, and society should explore targeted health promotion interventions tailored to adolescents’ psychosocial factors and characteristics, and provide support programs to promote the development of healthy behaviors.